MOTIVATIONAL CLIMATE AS THE REALIZATION MECHANISM OF YOUNG SCIENTISTS’ POTENTIAL IN BUSINESS ENVIRONMENT - Т. Shkoda; M. Tepliuk; I. Riepina; I. Semenets-Orlova; O. Domina (Фінансово-кредитна діяльність: проблеми теорії та практики, 2021)
Abstract. Modern young scientists as representatives of the professional community of scientists now need to develop new mechanisms for realizing their potential in a business environment that is experiencing an extremely turbulent period of its development. The main purpose of this article is to comprehensively study the motivational climate as the mechanism for realizing the potential of young scientists in the business environment, which will have a positive aspect for stakeholders. The study found that the scientific achievements of most scientists are undoubtedly important for the formation of theoretical foundations for the development of a motivational mechanism, however, scientists do not single out the motivational tools for realizing the potential of young scientists, although they confirm in their researches the relationship between motivation, motivational climate and education. It is determined that the main tasks of personnel motivation are to involve staff in the organization, retain employees and ensure their loyalty to the business environment where they work, stimulate productive behaviour, control labour costs, ensure administrative efficiency, simplicity and clarity to each employee. The proposals of the authors are formed on a set of criteria for diagnosing the motivational climate of the enterprise, which will lead to constant updating and improvement of operational activities of enterprises, and effective engagement of promising young researchers as employees or partners. The algorithm of evaluating the motivational climate of the enterprise is offered in the work, which includes three stages: preparatory, evaluative, analytical. For making general evaluation it is proposed to use the index of motivational climate, which has such elements as the importance of the i-th criterion of the motivational climate of the enterprise; score assessment of the strength of motivation of the i-th criterion; and score assessment of employee satisfaction with the i-th criterion. Such evaluation of the enterprise motivational climate is important for realizing the young scientists’ potential as it gives them the possibility to evaluate if the enterprise is perspective for the future cooperation.